The relationship between physical activity and depression, anxiety, and stress in college students: a mediating effect of diet - Jiazhi, Sheng; Caixia, Chen; Lamei, Gong; Jian, Zhou (Frontiers in Nutrition, 2025)
ObjectivePrevious studies have demonstrated that engaging in physical activity is a vital behavioral element in mitigating experiences of depression, anxiety, and stress. However, the specific mechanisms by which dietary practices and physical activity interact to affect these psychological conditions are not fully understood. Thus, this study aimed to comprehensively examine the relationships between physical activity, diet, and mental health outcomes, specifically depression, anxiety, and stress, among college students and to elucidate the pathways through which these factors interact.MethodThis study analyzed 1,076 college students (18.8 ± 0.8 years old) via the Adult Dietary Behavior Questionnaire (covering eight dimensions), the physical activity scale, and the depression-anxiety-stress scale.ResultsThere were significant differences in dietary behavior and physical activity parameters between male and female college students; however, no significant differences were observed in levels of depression, anxiety, or stress. The dimensions of college students' dietary behavior were significantly correlated with symptoms of anxiety, stress, and depression (p < 0.01). Higher levels of physical activity were negatively correlated with anxiety, stress, and depression symptoms in college-aged students (p < 0.01). Dietary behavior was significantly correlated with college students' physical activity. Through structural equation modeling analysis, our findings revealed that physical activity not only directly reduced depression, stress, and anxiety among college students but also indirectly alleviated them by improving their dietary behaviors. The direct effects of physical activity on depression, anxiety, and stress in college students were greater than the mediating effects of dietary behavior.ConclusionRegular physical activity plays a key role in reducing depression, anxiety, and stress among college students, with dietary behavior serving as a mediating factor. Therefore, promoting exercise and healthy eating within university settings is recommended for better mental health. Future research should investigate this relationship across diverse populations to gain valuable insights into mental health interventions.